Detection of early decayed oranges by structured-illumination reflectance imaging coupling with texture feature classification models - Cai, Zhonglei; Huang, Wenqian; Wang, Qingyan; Li, Jiangbo (Frontiers in Plant Science, 2022)
Citrus fruits are susceptible to fungal infection after harvest. To reduce the economic loss, it is necessary to reject the infected citrus fruit before storage and transportation. However, the infected area in the early stage of decay is almost invisible on the fruit surface, so the detection of early decayed citrus is very challenging. In this study, a structured-illumination reflectance imaging (SIRI) system combined with visible LED (Light Emitting Diode) lamp and monochrome camera was developed to detect early fungal infection in oranges. Under sinusoidal modulation illumination with spatial frequencies of 0.05, 0.15 and 0.25 cycles mm-1, three phase shifted images with phase offsets of -2 π/3, 0 and 2π /3 were acquired for each spatial frequency. The direct component (DC) and amplitude component (AC) images were then recovered by image demodulation using a three-phase-shifting approach. Compared with DC image, the decayed area can be clearly identified in AC image and RT image (AC/DC). The optimal spatial frequency was determined by analyzing the AC image and pixel intensity distribution. Based on the texture features extracted from DC, AC and RT images, four kinds of classification models including partial least square discriminant analysis (PLS-DA), support vector machine (SVM), least squares-support vector machine (LS-SVM) and k-nearest neighbor (KNN) were established to detect the infected oranges, respectively. Model optimization was also performed by extracting important texture features. Compared among all models, the PLS-DA model developed based on eight texture features of RT images achieved the optimal classification accuracy of 96.4 %. This study showed for the first time that the proposed SIRI system combined with appropriate texture features and classification model can realize the early detection of decayed oranges.